Mood and neural correlates of excessive daytime sleepiness in Parkinson's disease. (7th November 2016) - Wen, M.‐C.; Chan, L. L.; Tan, L. C. S.; Tan, E. K.
Abstract : For patients with Parkinson's disease (PD), excessive daytime sleepiness (PD‐EDS) is a debilitating non‐motor symptom and may be affected by mood symptoms, especially depression and anxiety. Few neuroimaging works have attempted to identify the neural features of PD‐EDS, but various findings were reported. The purpose of this study was to systematically review the literature on mood and neuroimaging correlates of PD‐EDS. A MEDLINE, PubMed, EMBASE, and PsycInfo search for peer‐reviewed original research articles on depression, anxiety, and neuroimaging in PD‐EDS identified 26 studies on depression, nine on anxiety, and eight on neuroimaging. Half of the studies reported greater depression in PD‐EDS‐positive patients compared with PD‐EDS‐negative patients. There was a significantly positive correlation between depression and PD‐EDS. Limited studies on anxiety in PD‐EDS suggested a weak correlation between anxiety and EDS. For depression and anxiety, the effect sizes were medium when EDS was subjectively measured, but became small when EDS was objective measured. Current neuroimaging studies generally suggested diminished neural structural and functional features (eg, brain volume, white matter integrity as indicated by fractional anisotropy, and cerebral metabolism) in patients with PD‐EDS. Future studies should apply objective and subjective measures of mood symptoms and EDS and improve the neuroimaging methodology via using multimodal techniques and whole‐brain analysis to provide new clues on the mood and neural correlates of PD‐EDS.